Simultaneous measurement stable and radiogenic Nd isotopic compositions by MC-ICP-MS with a single-step chromatographic extraction technique. Issue 12 (8th November 2021) - Bai, Jiang-Hao; Liu, Fang; Zhang, Zhao-Feng; Ma, Jin-Long; Zhang, Le; Liu, Yu-Fei; Zhong, Song-Xiong; Wei, Gang-Jian
Abstract : A single TODGA resin column to isolate Nd from geological samples. Abstract : Removing interferences such as Ce on Nd isotopes during column chemistry is hard to achieve due to their similar properties. In this study, we established a simple but efficient Nd separation technique with the perfect separation of Nd from Ce and nearly 100% Nd yield using the TODGA resin (50–100 μm, Eichrom, USA) after actual measurements. All samples used here through the Nd separation technique have Ce/Nd ratios less than 0.003. The whole procedure takes about 10 h. The stable Nd isotopes were measured by MC-ICP-MS and calibrated with standard-sample-standard bracketing (SSB) combined Eu internal normalization. The potential influences of Eu and Ce on stable Nd isotopic analysis were strictly evaluated. The long-term analyses of the JNdi-1 standard produced a total average δ 142/144 Nd of 0.000 ± 0.029‰ (2SD, n = 210), δ 145/144 Nd of 0.000 ± 0.029‰ (2SD, n = 210), and δ 146/144 Nd of 0.000 ± 0.027‰ (2SD, n = 210). Two pure Nd standards, La Jolla and Nd-GIG, produced δ 146/144 Nd values (means ± 2SD, n = 20) of −0.227 ± 0.030‰ and 0.226 ± 0.021‰, respectively. δ 146/144 Nd (means ± 2SD, n = 20) of seven geological reference materials (BCR-1, BHVO-2, AGV-2, GSP-2, NOD-P-1, NOD-A-1, and GBW07249) were also reported. The reproducibility of δ 146/144 Nd was better than 0.030‰. These results are in good agreement with the published DS-TIMS methods. In addition, our method also allows the concurrent determination of the radiogenic 143 Nd/ 144 Nd ratio. All the 143 Nd/ 144 Nd ratios of these samples are identical with the preferred values published in the GeoReM Database. These results indicated that the method of Nd isotopic analysis established here can simultaneously measure high-precision δ 142/144 Nd, δ 145/144 Nd, δ 146/144 Nd, and radiogenic 143 Nd/ 144 Nd ratio for geological materials.